Association of rodents with man-made infrastructures and food waste in Urban Singapore. Issue 1 (31st December 2022) - Oh, Hui Yun Penny; Humaidi, Mahathir; Chan, Qian Yi; Yap, Grace; Ang, Kai Yang; Tan, Jason; Ng, Lee Ching; Mailepessov, Diyar
ABSTRACT: Background: Rodent population control is an important measure in reducing the risk of rodent-borne disease transmission. In this study, we examined rodent activity in the sanitary waste network around the household waste-collection bin chamber of an urban residential apartment block. Methods: We utilised infra-red camera traps to determine the pattern of rodent activity in a rodent-infested bin chamber and its associated sanitary waste network. Multivariable logistic regression was performed to assess the risk factors that were independently associated with rodent activity in the bin chambers. Result: The camera trap surveillance showed that the rodents were active in the bin chamber and sanitary network both in the day and at night. In the cross-sectional study, rodent activity in the bin chambers was independently associated with broken floor traps [Adjusted odds ratio (AOR): 36.7, CI: 21.3–66.3], calendar month [Log-likelihood ratio test (LRT) p = 0.002] and Town Council [LRT p = 0.004] variables. In restricted analysis, rodent activity in bin chambers was independently associated with defects in the wastewater pipe under the chamber [AOR: 12.3, CI: 4.3–51.7]. Conclusion: Our study suggests that urban municipal management councils should prioritize rodent control resources in areas according to the factors that increase the risk of rodent infestation.